2007
DOI: 10.1089/apc.2007.9985
|View full text |Cite
|
Sign up to set email alerts
|

Type and Pattern of Illicit Drug Use and Access to Health Care Services for HIV-Infected People

Abstract: Approximately 28% of HIV-infected people in treatment in the United States report using illicit drugs. Illicit drug users have poorer course of HIV disease than non-drug users, which is thought to be due to their irregular use of HIV medical services. We examined associations between type (cocaine versus opioids) and pattern of drug use (drug use at baseline, 6-month follow-up, both periods, and nonuse) and health care utilization for a large sample of HIV-infected individuals drawn from a multisite project th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
61
2
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(67 citation statements)
references
References 38 publications
3
61
2
1
Order By: Relevance
“…17 For example, in persons with HIV, substance use disorders are barriers that significantly decrease adherence to medical care, [18][19][20][21] whereas treatment, specifically agonist medication for opioid dependence, results in increased adherence in people with HIV. 22,23 Patients with co-occurring substance use and HIV use higher levels of emergency room and inpatient services and have longer lengths of inpatient stays than other HIV-infected persons, 24,25 although opioid agonist treatment is associated with reduced acute care utilization.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…17 For example, in persons with HIV, substance use disorders are barriers that significantly decrease adherence to medical care, [18][19][20][21] whereas treatment, specifically agonist medication for opioid dependence, results in increased adherence in people with HIV. 22,23 Patients with co-occurring substance use and HIV use higher levels of emergency room and inpatient services and have longer lengths of inpatient stays than other HIV-infected persons, 24,25 although opioid agonist treatment is associated with reduced acute care utilization.…”
mentioning
confidence: 99%
“…34 Subjects in the sample who used drugs were less likely than non-users to have received optimal levels of HIV primary care and more likely to use emergency care. 35 When this population was compared with patients from the HIV Cost and Services Utilization Study (HCSUS), a national sample of HIV-infected persons, they were found to be significantly more likely to be heavy alcohol users and significantly less likely to use ambulatory medical care services. 36 While they may obtain medical care via their use of inpatient and emergency care, PSUDs also often do not receive the addiction treatment services they need.…”
mentioning
confidence: 99%
“…Further, alcohol and other drug use is high among HIV-infected individuals, with the only national prevalence study of HIV-infected adults in the US reporting that 26% were using illicit drugs other than marijuana without meeting criteria for dependence, and another 13% met criteria for drug dependence (including marijuana) within the last 12 months [87]. In a more recent multisite study of nearly 1,000 HIV-infected individuals, 40% reported cocaine or heavy alcohol use and 25% reported use of two or more illicit drugs (excluding alcohol or marijuana) in the past year [88]. Some studies in this review sought to account for these confounds by reporting mental health diagnoses or attempting to exclude individuals currently using other drugs, and this matching is important when making group comparisons.…”
Section: Critique Of the Current Literature And Future Research Priormentioning
confidence: 99%
“…About 28% of all HIV-positive US patients in treatment report using illicit drugs [43]. This proportion may be higher among those who are not in care [44]. Using a structured clinical interview, 50% of patients in the past year and 33% in the past month reported a psychiatric comorbidity [45].…”
Section: Patients With Substance Abuse and Psychosocial Disordersmentioning
confidence: 99%
“…Using a structured clinical interview, 50% of patients in the past year and 33% in the past month reported a psychiatric comorbidity [45]. Psychiatric comorbidity in PLWHA was shown to increase sexual risk-taking, substance abuse, poor medication adherence, relational abuse, and other maladaptive behaviors [43,44,46,47]. Poorer immune and metabolic functioning was also attributed to substance abuse among PLWHA [44,45].…”
Section: Patients With Substance Abuse and Psychosocial Disordersmentioning
confidence: 99%